2017
DOI: 10.1111/pcn.12528
|View full text |Cite
|
Sign up to set email alerts
|

Application of induced pluripotent stem cells to understand neurobiological basis of bipolar disorder and schizophrenia

Abstract: The etiology of neuropsychiatric disorders, such as schizophrenia and bipolar disorder, usually involves complex combinations of genetic defects/variations and environmental impacts, which hindered, for a long time, research efforts based on animal models and patients' non-neuronal cells or post-mortem tissues. However, the development of human induced pluripotent stem cell (iPSC) technology by the Yamanaka group was immediately applied to establish cell research models for neuronal disorders. Since then, tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 230 publications
(271 reference statements)
0
15
0
1
Order By: Relevance
“…In studies using iPSC‐derived neurons derived from BD patients, increased expression of genes involved in ventralization, decreased WNT signaling, and altered expression of genes involved in RNA metabolism were reported . In a study in which hippocampal dentate gyrus granule cells prepared from iPSC of six BD patients (three lithium responders and three non‐responders) were analyzed, patients’ neurons were found to have changes in mitochondrial function, such as increased mitochondrial membrane potential, decreased mitochondrial size, and increased expression of mtDNA‐derived transcripts.…”
Section: Patient‐derived Cellsmentioning
confidence: 99%
“…In studies using iPSC‐derived neurons derived from BD patients, increased expression of genes involved in ventralization, decreased WNT signaling, and altered expression of genes involved in RNA metabolism were reported . In a study in which hippocampal dentate gyrus granule cells prepared from iPSC of six BD patients (three lithium responders and three non‐responders) were analyzed, patients’ neurons were found to have changes in mitochondrial function, such as increased mitochondrial membrane potential, decreased mitochondrial size, and increased expression of mtDNA‐derived transcripts.…”
Section: Patient‐derived Cellsmentioning
confidence: 99%
“…Mounting research using patient-derived iPSCs has proposed several cellular pathways altered in these psychiatric disorders, including synaptic function and Wnt signaling [ 8 ]. However, most of these studies differentiated the iPSCs into a predefined specific cell type.…”
Section: Introductionmentioning
confidence: 99%
“…Recent genome‐wide association studies have shown the utility of polygenic risk scores (PRS), and analyses using PRS have confirmed traditional clinical findings, for example, early age at onset in major depression as a risk factor of bipolar disorder . Moreover, development of induced pluripotent cell technology has enabled the analysis of patients’ neurons in vitro for the first time …”
mentioning
confidence: 91%
“…However, such remarkable progress has not yet caused innovation in clinical practice in psychiatry, and daily practice in clinics is mostly similar to that of several decades ago. Paradoxically, the progress of biological research has obscured the boundary of diagnostic categories: The same classes of drugs are effective for different types of diseases and there is an overlap in genetic, neuroimaging, and cellular findings across different mental disorders . This may indicate that current biological studies in psychiatry have not grown out of understanding mental disorders’ symptomatic‐level phenomena.…”
mentioning
confidence: 99%